Superconducting Properties in Arrays of Nanostructured β-Gallium - Moura, K. O. (2017)
Samples of nanostructured β-Ga wires were synthesized by a novel method of metallic-flux nanonucleation. Several superconducting properties were observed, revealing the stabilization of a weak-coupling type-II-like superconductor (Tc Tc≈ 6.2 K) with a Ginzburg-Landau parameter κGL G L = 1.18. This contrasts the type-I superconductivity observed for the majority of Ga phases, including small spheres of β-Ga with diameters near 15 μm. Remarkably, our magnetization curves reveal a crossover field HD H D, where we propose that the Abrikosov vortices are exactly touching their neighbors inside the Ga nanowires. A phenomenological model is proposed to explain this result by assuming that only a single row of vortices is allowed inside a nanowire under perpendicular applied field, with an appreciable depletion of Cooper pair density at the nanowire edges. These results are expected to shed light on the growing area of superconductivity in nanostructured materials.